Avaliação da funcionalidade e qualidade de vida em indivíduos com doença pulmonar obstrutiva crônica - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
This study aimed to analyze how the level of airflow obstruction affects the functional level and quality of life (QOL) in patients with Chronic Obstructive Pulmonary Disease (COPD) and how different types of rehabilitation can influence QOL. To this end, a dissertation was written in multipaper format. Firstly, a systematic literature review was carried out, with the aim of analyzing the studies that investigated QoL in COPD patients who participated in rehabilitation programs, using the Methodi Ordinatio. A cross-sectional observational study was then carried out with 34 individuals diagnosed with COPD according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) criteria; FEV1/FVC ratio < 0.70 after bronchodilator use using spirometry; with disease severity according to GOLD 2 (moderate), GOLD 3 (severe) or GOLD 4 (very severe) airflow obstruction, between January 2023 and November 2023. The following questionnaires were used: the 26-question World Health Organization Quality of Life (WHOQOL-Bref) and the modified version of the Pulmonary Functional Status and Dyspnea Questionnaire (PFSDQ-M). This was done by interview. The chi-square test, factorial anova test, Kruskal-Wallis, independent t-test and ordinal logistic regression were used for statistical analysis, with a significance level of 95%. As a result, 16 studies were found in the systematic review. The results indicate a large difference in InOrdinatio values (ranging from 315.75 to 55.85). Of the studies listed using the Methodi Ordinatio, half showed better levels of QoL in the intervention group, mostly long-term combined intervention programs. There were large differences in the frequency of training and a lack of information about the intensity of training. The field research showed that there were no significant differences between GOLD levels in QoL, a result that remained after analysis adjusted for independent variables. Regarding functionality, patients with worse airflow obstruction had worse functional levels, but age, non-smoking habits, frequency of physical activity (PA), exercise capacity and muscle strength had positive effects on functionality in GOLD 4 patients. Thus, it can be concluded that the review showed that the studies revealed that a combined therapy had better levels of QoL in individuals with COPD. However, it is necessary to analyze the results with caution since, in addition to the different frequencies, the lack of information about the treatments hinders a more reliable analysis. With regard to the field study, individuals with COPD had a poor overall QoL, regardless of GOLD level. However, in terms of functionality, people with more severe airflow obstruction had worse functional levels. However, lifestyle habits such as quitting smoking and practicing PA improved functionality and indirectly QoL, even at the most severe levels of the disease.
Keywords: qualidade de vida; doença pulmonar obstrutiva crônica; limitação física; reabilitação; quality of life; pulmonary disease chronic obstructive; physical limitation; rehabilitation; CNPQ::CIENCIAS DA SAUDE